SEBARAN DAN PROSES GEOLOGI PEMBENTUKAN LAVA TUBE KESAKSAK DI BATUR UNESCO GLOBAL GEOPARK - Ida Bagus Oka Agastya; Putu Diyan Diwyastra; Suryo Hespiantoro; Dewa Ariana (PPSDM Geominerba, 2023)
Batur Volcano is an active stratovolcano located at Bali, in the area belongs to Batur Caldera as the the first UNESCO Global Geopark in Indonesia. Batur volcano produced lava, there are nine lava deposits resulting from the eruption of Mount Batur from 1849-1974. Many studies have been conducted to determine petrogenesis and the history of the eruption of Batur volcano, however, a more comprehensive study has never been carried out on the product of lava flows in the form of Lava Tubes/lava caves at Batur volcano. The research of Lava Tube focuses on the east side of Batur volcano where the 1888 lava flowed. Therefore, wecarried out field observation and analysis to interpret of the genesis Lava Tubes formation at Batur volcano. The Kesaksak Lava Tube at Batur Volcano was formed from the 1888 eruption of Batur Volcano, and the morphology forming tumuli which is referred to the tumulus cave lava. The lava flow that forms tumuli lava is caused by the rapid cooling of the lava surface then develops into a Lava Tube to form a lava flow further towards Lake Batur. The 1888 lava flow had a basalt composition with the character of the a'a lava. This supports the fact that the Lava Tube was not only formed in the pahoehoe lava flow. As one of the geosites in the Batur UNESCO Global Geopark area, the KesaksakLava Tube geosite has the potential to be developed as a geotourism object through the development of a geotrail that connects several geodiversities, biodiversity and cultural diversity in the Batur UNESCO Global Geopark area.